Transnational Muslim Americans: four women in Jordan - Curtis, Edward E. (Marburg journal of religion, 2013)
This article examines the biographies of four Muslim American women who have lived in Amman, Jordan. It seeks to understand how residency in this Muslim-majority country in the Middle East has affected their religious attitudes and practices as well as their gender, ethnic, and national identities. In offering analysis of these women’s own thinking about how their time in Jordan had or had not altered their Muslim and American identities and practices, this article contributes to larger scholarly conversations about religion and politics in transnational perspective. The travel and observations of these four women in Amman evidenced the often unpredictable nature of personal change when a human being moves, both physically and spiritually, from one place to another. Their stories confirm that the focus of much social scientific literature on transnationalism on how institutions—both formal and informal, state and non-state--delimit, constrain, and shape political identity is useful and necessary in understanding transnational ventures. But it also shows that such literature does not always account for the possible religious meanings of human movement. The transnational Muslim Americans in this study engage in ethical and cosmic, national and transnational practices all at once. Their stories show how an account sensitive to religious activity can helpfully account for the multiple meanings of transnational practice among Muslim Americans.